What's in a model? Network models as tools instead of representations of what psychiatric disorders really are. (2019) - van Loo, Hanna M.; Romeijn, Jan-Willem
Abstract: Network models block reductionism about psychiatric disorders only if models are interpreted in a realist manner – that is, taken to represent "what psychiatric disorders really are." A flexible and more instrumentalist view of models is needed to improve our understanding of the heterogeneity and multifactorial character of psychiatric disorders.